Quality Control in Small and Medium Enterprises: A Study of Present Challenges and Future Opportunities - Widaningrum, Dyah Lestari; Meilia, Amelia; Charis, Samuel Nata; Ariyanti, Fransisca Dini; Amrina, Uly (Journal of Applied Engineering and Technological Science (JAETS), 2025)
Quality control is a critical foundation for establishing effective and efficient systems across industries, but small and medium enterprises (SMEs) face unique challenges in implementing effective quality control due to resource constraints. This study aims to identify the specific needs through demographic and operational analysis, and to develop a compact, adaptable Quality Management Framework to enhance their operational excellence. Survey responses from 50 SME managers were analyzed using cluster analysis, utilizing Ward's method and K-means to categorize businesses based on their quality control practices. Findings revealed three distinct SME clusters emerged, with systematic quality practices correlating to 71% higher customer satisfaction. These findings highlight significant variations in managerial perceptions, needs, and priorities.  This research proposes an adaptable quality management framework tailored for SMEs and recommends the integration of technology to enhance scalability and effectiveness. Thus, this study addresses a theoretical gap in SME quality control system design while offering practical, actionable insights for enhancing quality management processes in diverse industrial contexts.